Problem-solving strategies for efficient and elegant solutions, grades 6-12 : a resource for the mathematics teacher - Posamentier, Alfred S., 1942-; Krulik, Stephen, ....-; Hauptman, Herbert A., ....- (Thousand Oaks (Cal.) : Corwin Press, 2008)
Demonstrating there is always more than one approach to solving a problem, well-known authors and educators Alfred S. Posamentier and Stephen Krulik present ten basic strategies that are effective for finding solutions to a wide range of mathematics problems. These tried-and-true methods—including working backwards, finding a pattern, adopting a different point of view, solving a simpler analogous problem, and making a visual representation—make problem solving easier, neater, and more understandable for students as well as teachers. Providing numerous sample problems that illustrate how mathematics teachers and specialists can incorporate these techniques into their mathematics curriculum, this updated edition also includes: •A variety of new problems that show how to use the strategies •References to current NCTM standards •Solutions to the problems in each chapter •Extensive discussions of the empowering strategies used to solve sample problems The second edition of Problem-Solving Strategies for Efficient and Elegant Solutions, Grades 6–12 helps teachers develop students' creative problem-solving skills for success in and out of school.
Introduction to problem-solving strategies -- Working backwards -- Finding a pattern -- Adopting a different point of view -- Solving a simpler analogous problem -- Considering extreme cases -- Making a drawing (visual representation) -- Intelligent guessing and testing (including approximation) -- Accounting for all possibilities -- Organizing data -- Logical reasoning.
Includes bibliographical references (p. 249-260).
Keywords: Probleemoplossend denken; Problem solving; Wiskunde